2019
DOI: 10.1186/s12957-019-1602-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreduction plus hyperthermic intraperitoneal chemotherapy for peritoneal carcinomatosis in colorectal cancer patients: a single-center cohort study

Abstract: Background In this study, we report our experience of cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) in patients with peritoneal carcinomatosis (PC) from colorectal cancer (CRC), focusing on the factors affecting survival. Methods All patients with surgically treated PC from colorectal cancer and with no involvement of other organs referred to our institute from March 2005 to December 2017 were included in the analysis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
1
15
0
4
Order By: Relevance
“…Close attention has been given to the morbidity and mortality associated with the CRS + HIPEC procedure. Our institution con rmed that the grade 3-4 morbidity rate and mortality rate after CRS + HIPEC were 24.3% and 0%, respectively, which is basically consistent with the results reported by international centres [7,[23][24][25][26] . Notably, we also found that patients with PM of rectal origin were more likely to develop grade 3-4 postoperative complications after CRS + HIPEC than patients with PM of colonic origin (38.9% vs 19.2%, P = 0.094), but this difference was not statistically signi cant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Close attention has been given to the morbidity and mortality associated with the CRS + HIPEC procedure. Our institution con rmed that the grade 3-4 morbidity rate and mortality rate after CRS + HIPEC were 24.3% and 0%, respectively, which is basically consistent with the results reported by international centres [7,[23][24][25][26] . Notably, we also found that patients with PM of rectal origin were more likely to develop grade 3-4 postoperative complications after CRS + HIPEC than patients with PM of colonic origin (38.9% vs 19.2%, P = 0.094), but this difference was not statistically signi cant.…”
Section: Discussionsupporting
confidence: 90%
“…At present, most literature has demonstrated that a high peritoneal cancer index (PCI), incomplete cytoreduction, young age and postoperative complications are poor prognostic factors after CRS + HIPEC [9][10][11][12] . It has been well established that different primary tumour locations have different biological behaviours and prognoses [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 7 ] This is especially important for small lesions that are difficult to detect by CT, conventional MRI, and PET-CT. [ 9 ] Patients detected with PMs might benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. [ 26 , 27 ] The present meta-analysis revealed that DWI had 89% pooled sensitivity (95% CI: 83%–93%) and 86% pooled specificity (95% CI: 79%–91%) for the diagnosis of PMs from various abdominal cancers.…”
Section: Discussionmentioning
confidence: 69%
“…As can be concluded from the intersection of the aforementioned studies, the completeness of cytoreduction, surgeon experience and center expertise are the common key elements to survival benefit regardless of tumor origin. Therefore, developing proficiency in PSM surgery is the most crucial step in implementing a CRS and HIPEC specialized program [ 25 ].…”
Section: Discussionmentioning
confidence: 99%